PELAKSANAAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA DI PT. BIAS NUSATAMA PEKANBARU - Nadila Oktaviani; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Occupational health and safety program is one of an important part that should be introduced in project implementation in the field of well service and the warehouse. The risk of an accident and occupational disease often occurred because of human resources who do not implement the occupational helath and safety program well. However this can impact on decreasing productivity level of workers and losses to Company.This research aims to known about the implementation of occupational health and safety program and the factors that affect the implementation OHS program in PT. Bias Nusatama Pekanbaru. This research using methods descriptive qualitative with data collecting technique in the form of an interview, observation and a study literature.Research of the results is the implementation of occupational health and safety program in PT. Bias Nusatama Pekanbaru not run well this is because the disobedience of employees against the rules given and not running of routine procedures and not the achievement of the goal of the program which is zero accident. Factors that affect the implementation of OHS is the minimum of quantity a human resources which owned by the Company and Department of Labor and bureaucratic structure that does not run efficiently by employees in carrying out standart operating procedure (SOP).Keywords : Occupational Health and Safety, Program, Routine Procedure